Any nonzero number raised to the zeroth power is 1, so `28^0=1.` This is a definition and it's made so that certain patterns hold and the laws of positive exponents carry over to zero and negative exponents.
`28^1=28=784/28`, so the pattern suggests defining
Another way to view it:
For positive exponents, `x^m/x^n=x^(m-n).` Using this we get
`1=28^1/28^1=28^(1-1)=28^0.` Again, this suggests that we should define `28^0` to be 1. This same reasoning can be used to define negative exponents in a consistent way.
Back to the original problem, we have `9(28^0)=9(1)=9.`
because any number to the zero power is 1...therefore 9x1=9
because ANYTHING raised to the power of zero is 1,and one being in the bracket,9x1=9